Patterns Of Relationships Between Verbal Memory, Language, And Verbal Intelligence In Preschoolers - Rexsy Taruna (Poltekkes Kemenkes Surakarta, 2021)
Background: This study aims to identify whether language can be the mediator of the relation between verbal memory and verbal intelligence Methods: The participants that involved in this study are 51 preschool-age children in Pekanbaru, consisting of males (n=24) and females (n=27), ages four to six years. Cluster sampling technique was used to collect the sample. The abilities of verbal memory, language and verbal intelligence were assessed towards each participant individually. Wechsler Preschool and Primary Scale of Intelligence, Test of Auditory Processing Skill 3 and Developmental Profile 3 were assigned as the instrument of the test conducted in this study. Data analysis in this study uses mediator analysis. Results: This study found a positive correlation between verbal memory and verbal intelligence (r = 0.53; p<.05), language and verbal intelligence (r = 0.71; p<.05), language and verbal memory (r = 0.64; p<.05). Conclusion: According to the result of the analysis, it is evident that language can be the mediator of the relation between verbal memory and verbal intelligence.